2022
DOI: 10.3389/fvets.2022.1016970
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and risk factors of avian influenza A(H5) and A(H9) virus infection in pigeons and quail at live bird markets in Bangladesh, 2017–2021

Abstract: The avian influenza virus (AIV) impacts poultry production, food security, livelihoods, and the risk of transmission to humans. Poultry, like pigeons and quail farming, is a growing sector in Bangladesh. However, the role of pigeons and quails in AIV transmission is not fully understood. Hence, we conducted this study to investigate the prevalence and risk factors of AIV subtypes in pigeons and quails at live bird markets (LBMs) in Bangladesh. We collected oropharyngeal and cloacal swab samples from 626 birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Vendors purchasing waterfowl from a wholesale market instead of farms, and mixing healthy and sick birds as well as new birds with unsold birds, had a significantly higher risk to be positive for AIV. In contrast to Negovetich et al (2011), Islam et al (2022 found the likelihood of AIV detection to be 4.19 times higher in sick and deceased birds compared to healthy ones. They concluded that proper hygienic practices were not maintained and recommended improving biosecurity practices at live bird markets (Islam et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Vendors purchasing waterfowl from a wholesale market instead of farms, and mixing healthy and sick birds as well as new birds with unsold birds, had a significantly higher risk to be positive for AIV. In contrast to Negovetich et al (2011), Islam et al (2022 found the likelihood of AIV detection to be 4.19 times higher in sick and deceased birds compared to healthy ones. They concluded that proper hygienic practices were not maintained and recommended improving biosecurity practices at live bird markets (Islam et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
“…In contrast to Negovetich et al (2011), Islam et al (2022 found the likelihood of AIV detection to be 4.19 times higher in sick and deceased birds compared to healthy ones. They concluded that proper hygienic practices were not maintained and recommended improving biosecurity practices at live bird markets (Islam et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
“…LBMs are a significant source of AIV circulation, mutation, and spillover to humans or other wildlife. Over the past years, several studies have demonstrated a rising trend in AIV circulation among LBMs in Bangladesh ( 4 , 46 ). However, these studies have almost exclusively targeted urban settings ( 7 , 14 , 22 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Avian influenza viruses (AIVs) are zoonotic viruses that can infect domestic and wild bird species, along with a variety of other animals (1). Multiple subtypes of low pathogenic avian influenza (LPAI) viruses and highly pathogenic avian influenza (HPAI) have been detected from live bird markets (LBMs) and farms around Bangladesh, with H9N2 and H5N1 being the most prevalent (2)(3)(4). H5N1 and H9N2 are mostly endemic to countries in Southeast Asia, such as Bangladesh (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation